FEEDING MANAGEMENT AND BROODSTOCK PERFORMANCE OF BARRAMUNDI (Lates calcarifer): A CASE STUDY FROM TELUK BUO HATCHERY, INDONESIA - Indra Lesmana; Nur Aini; Rodhi Firmansyah (Universitas Mataram, 2025)
Barramundi (Lates calcarifer) is a high-value aquaculture species whose productivity strongly depends on the quality of broodstock management. In many government-operated hatcheries in Indonesia, feeding practices rely heavily on locally available trash fish without standardized supplementation, potentially affecting broodstock performance and water quality. This study aimed to document and evaluate feeding management practices for barramundi broodstock at the Teluk Buo Hatchery, West Sumatra, Indonesia. A descriptive case study was conducted over a one-month period through direct observation of feeding schedules, broodstock biometric data, and water quality monitoring. Broodstock were fed trash fish and squid at 3% biomass twice daily, supplemented with vitamins C, B-complex, and E on a scheduled basis. The broodstock ranged from 1.5–1.8 kg (males) and 5.7–6.5 kg (females), meeting recommended criteria for reproductive readiness. Water quality remained within optimal ranges (temperature 30.2–31.8 °C, salinity 30–33 ppt, pH 7–8, dissolved oxygen 5.5–6.3 mg/L), in compliance with national standards. These results indicate that structured feeding management contributes to broodstock health, gonadal maturation, and environmental stability. The findings provide a practical, replicable model for coastal hatcheries operating under resource-limited conditions and highlight the need for future studies addressing reproductive performance, economic feasibility, and sustainable feed alternatives.